Clinical, imaging and follow‐up study of optic neuritis associated with myelin oligodendrocyte glycoprotein antibody: a multicentre study of 62 adult patients. (20th October 2019) - Shor, N.; Aboab, J.; Maillart, E.; Lecler, A.; Bensa, C.; Le Guern, G.; Grunbaum, S.; Marignier, R.; Papeix, C.; Heron, E.; Gout, O.; Savatovsky, J.; et al.
Abstract: Background and purpose: There are few clinico‐radiological data on optic neuritis (ON) with myelin oligodendrocyte glycoprotein antibody (MOG‐IgG). The objective was to characterize the clinico‐radiological phenotype and outcome of patients with MOG‐IgG‐related ON. Methods: The records of all adult patients admitted in three medical centres with MOG‐IgG‐associated ON who underwent orbital and brain magnetic resonance imaging (MRI) at the acute phase were reviewed. Spinal cord MRI within 1 month from the ON and all of the follow‐up MRI were reviewed. Results: Of 62 patients, 41.9% had bilateral ON and 66.2% optic disc swelling. On initial MRI, lesions were anterior (92%), extensive (63%) and associated with optic perineuritis (46.6%). Silent brain lesions were found in 51.8% of patients but were mainly non‐specific (81%). Of 39 individuals with spinal MRI at onset, nine had abnormal findings (four were asymptomatic). Two symptomatic patients had longitudinally extensive myelitis with concurrent H‐sign. At last follow‐up, 5% of patients had visual acuity ≤0.1. Brain MRI remained unchanged in 41 patients (87%). Conclusions: Our study supports a mostly benign ophthalmological course of MOG‐IgG‐associated ON, despite initially longitudinally extensive lesions and development of optic nerve atrophy on orbital MRI. Spinal MRI could be of interest in detecting silent suggestive lesions.